Protocol for a multicentre prehospital randomised controlled trial investigating tranexamic acid in severe trauma: the PATCH-Trauma trial. Issue 3 (15th March 2021) - Mitra, Biswadev; Bernard, Stephen; Gantner, Dashiell; Burns, Brian; Reade, Michael C; Murray, Lynnette; Trapani, Tony; Pitt, Veronica; McArthur, Colin; Forbes, Andrew; Maegele, Marc; Gruen, Russell L
Abstract : Introduction: Haemorrhage causes most preventable prehospital trauma deaths and about a third of in-hospital trauma deaths. Tranexamic acid (TXA), administered soon after hospital arrival in certain trauma systems, is an effective therapy in preventing or managing acute traumatic coagulopathy. However, delayed administration of TXA appears to be ineffective or harmful. The effectiveness of prehospital TXA, incidence of thrombotic complications, benefit versus risk in advanced trauma systems and the mechanism of benefit remain uncertain. Methods and analysis: The Pre-hospital Anti-fibrinolytics for Traumatic Coagulopathy and Haemorrhage (The PATCH-Trauma study) is comparing TXA, initiated prehospital and continued in hospital over 8 hours, with placebo in patients with severe trauma at risk of acute traumatic coagulopathy. We present the trial protocol and an overview of the statistical analysis plan. There will be 1316 patients recruited by prehospital clinicians in Australia, New Zealand and Germany. The primary outcome will be the eight-level Glasgow Outcome Scale Extended (GOSE) at 6 months after injury, dichotomised to favourable (GOSE 5–8) and unfavourable (GOSE 1–4) outcomes, analysed using an intention-to-treat (ITT) approach. Secondary outcomes will include mortality at hospital discharge and at 6 months, blood product usage, quality of life and the incidence of predefined adverse events. Ethics and dissemination: The study was approved by The Alfred Hospital Research and Ethics Committee in Victoria and also approved in New South Wales, Queensland, South Australia, Tasmania and the Northern Territory. In New Zealand, Northern A Health and Disability Ethics Committee provided approval. In Germany, Witten/Herdecke University has provided ethics approval. The PATCH-Trauma study aims to provide definitive evidence of the effectiveness of prehospital TXA, when used in conjunction with current advanced trauma care, in improving outcomes after severe injury. Trial registration number: NCT02187120 .